2011
DOI: 10.1007/s12265-011-9338-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Response to CRT in Narrow QRS Patients

Abstract: Previous studies suggest that CRT may benefit narrow QRS patients with mechanical dyssynchrony (MD). We conducted an acute and chronic study, evaluating the response of heart failure patients with a narrow QRS to cardiac resynchronization therapy (CRT). ESTEEM-CRT was a multi-center, single-arm, feasibility study that evaluated ICD-indicated, medically-optimized patients with EF ≤ 35%, NYHA class III heart failure, QRS duration <120 ms, and MD as defined by the standard deviation of time to peak systolic veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Importantly, LESSER-EARTH, like the Resynchronization Therapy in Normal QRS (RETHINQ) 14 and Evaluation of Screening Techniques in Electrically-Normal, MechanicallyDyssynchronous Heart Failure Patients (ESTEEM-CRT) 15 trials, relied on functional metrics and indexes of reverse remodeling as opposed to hard clinical outcomes such as mortality. Nevertheless, these studies have consistently failed to demonstrate a benefit from CRT in patients with a narrow QRS complex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, LESSER-EARTH, like the Resynchronization Therapy in Normal QRS (RETHINQ) 14 and Evaluation of Screening Techniques in Electrically-Normal, MechanicallyDyssynchronous Heart Failure Patients (ESTEEM-CRT) 15 trials, relied on functional metrics and indexes of reverse remodeling as opposed to hard clinical outcomes such as mortality. Nevertheless, these studies have consistently failed to demonstrate a benefit from CRT in patients with a narrow QRS complex.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these studies have consistently failed to demonstrate a benefit from CRT in patients with a narrow QRS complex. The primary outcome for RETHINQ 14 and ESTEEM-CRT 15 was maximum oxygen uptake (peak . Vo 2 ) as assessed by cardiopulmonary exercise testing, which has been criticized for its lack of sensitivity in detecting therapeutic responses, potential to be poorly tolerated by patients with HF, and need for careful calibration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, several single center studies have observed that CRT is effective in patients with QRS duration <120 or <130 ms in combination with mechanical dyssynchrony. [15][16][17][18] However, the 4 randomized studies in this field have consistently been neutral 19,20 or negative. 21,22 The RethinQ study randomized 172 patients to CRT or no CRT.…”
Section: Update Of Clinical Trialsmentioning
confidence: 99%
“…8 Small, randomized clinical studies that were not powered to assess clinically relevant outcomes [9][10][11][12][13][14] have suggested the existence of true clinical equipoise, thereby setting the stage for a definitive outcome trial. We therefore initiated the Echocardiography Guided Cardiac Resynchronization Therapy (EchoCRT) study to investigate the effect of CRT on morbidity and mortality among patients with symptomatic heart failure, a narrow QRS complex, and echocardiographic evidence of left ventricular dyssynchrony.…”
mentioning
confidence: 99%